Network reconfiguration and control for loss reduction using genetic algorithm - Jawad, Mohamed Hassan Izzaldeen (2010)
Power distribution networks typically have tie and sectionalizing switches whose states determine the topological configuration of the network. In this work a feeder reconfiguration algorithm is presented for the purpose of power loss reduction in distribution networks. The methodology developed a combined optimization technique. Also capacitor placement employing Genetic Algorithm is presented in achieving the proper arrangement of capacitor in a distribution network. The proposed algorithm has been implemented in technical MATLAB package and tested with two examples namely, 18- and 49-bus systems. All the data for 18-bus system test are taken from previous work, and all the data for 49-bus system test are taken from an existing Iraqi distribution network.